Análise da qualidade microbiológica do peixe (Eugerres brasilianus, Curvier 1830) e das águas do Estuário do Rio Itanhaém, SP, Brasil - Melo, Renata Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The bacterial microbiota found in live fish is directly related to the microbiota of the environmente, in the words, the microorganisms present in their body surface, gills, gastrointestinal tract and muscle are related to the same environment in which it is inserted. Fish naturally have a wide range of bacteria, which may also be commonly found in the water. However, the bacteria of fecal origin, such as E.coli and Enterococci, are not common inhabitants of the intestinal flora of fish, being his presence linked to contamination by human feces or other warm-blooded animals in the water capture. Thus, the monitoring of the microbiological quality of the water and the fish caught for human consumption, it is necessary, since they can cause harm to human health, causing public health problems. The objective of this study was to evaluate the microbiological quality of fish (Eugerres brasilianus, Curvier 1830) and waters of the estuary of the River Itanhaém, SP (Brazil). Three bacteria were used to assess the microbiological quality of water and fish, two of human fecal origin, Escherichia coli and Enterococci, and a source not fecal, Staphylococcus aureus, all obtained by membrane filtration. The fish were evaluated for their gills and muscle. The results showed that during the entire period of the study, the waters of the river Itanhaém presented within the limits set by legislation CONAMA resolution 357/05, however the use of E.coli, proved to be insufficient to assess the quality of the water, since the density of Enterococci was high throughout the study in all points analyzed. The analysis of fish, were found high concentrations for the three bacteria used, with the gills presenting with greater number in relation to the muscle. According to the RDC 12/05, the fish were evaluated during the study were unfit for consumption. In the proximity of the ETE-Anchieta, located to the left boarder of the river, the bacteria S.aureus was more ...

A microbiota bacteriana encontrada nos peixes vivos está diretamente relacionada à microbiota do ambiente, ou seja, os microrganismos presentes em sua superfície corporal, brânquias, trato gastrointestinal e musculatura estão relacionados aos mesmos do ambiente em que está inserido. Os peixes possuem naturalmente uma vasta gama de bactérias, que também podem ser comumente encontradas na água. Porém, as bactérias de origem fecal, como E.coli e Enterococos, não são habitantes comuns da flora intestinal dos peixes, sendo sua presença atrelada à contaminação por fezes humanas ou de outros animais de sangue quente na água de captura. Sendo assim, o monitoramento da qualidade microbiológica tanto da água, quanto dos organismos retirados dela para consumo humano, tornam-se necessários, já que podem causar prejuízo a saúde do homem, provocando problemas de saúde pública. O objetivo deste estudo foi avaliar a qualidade microbiológica do peixe (Eugerres brasilianus, Curvier 1830) e das águas do estuário do Rio Itanhaém, SP (Brasil). Três bactérias foram utilizadas para avaliar a qualidade microbiológica da água e dos peixes, duas de origem fecal humana, Escherichia coli e Enterococcus sp. e uma de origem não fecal, Staphylococcus aureus, todas obtidas pela técnica da membrana filtrante. Nos peixes foram avaliados suas brânquias e músculo. Os resultados obtidos mostraram que durante todo o período do estudo, as águas do rio Itanhaém apresentaram-se dentro dos limites estabelecidos pela legislação CONAMA 357/05, porém o uso de E.coli, demonstrou ser insuficiente para avaliar a qualidade da água, visto que a densidade de Enterococcus sp. foi alta durante todo o estudo em todos os pontos analisados. Na análise dos peixes, foram encontradas altas concentrações para as três bactérias utilizadas, com as brânquias se apresentando com maior número em relação ao músculo. De acordo com a legislação RDC 12/01,...
Keywords: Micro-organismos; Peixe - Contaminação; Escherichia coli; Enterococcus; Staphylococcus aureus; Itanhaem, Rio (SP)